MEMBACA PEREMPUAN DARI TULANG RUSUK - Nurfaidah Resti (Multilingual, 2016)
Things on women's lives have always been discussed in various domains of life, suchas legal, economic, politic, or social. Those are also being the main discussion in theliterary world. Some authors in their own manner and perspective reveal sides ofwomen. However, most of them in literature shows that women are weak creatures asare being weakened by the pressure of various things, such as politics, culture, or thelaw. Women’s voice and movement are still underestimated by the dominant power. Itapplies universally, not least in China, the country which was known as a source ofvery high culture. The paper will explore conflicts of Feng whose life on the extremedifferent political situation on the novel The Flowers in Shanghai by Duncan Jepson.The analysis was based on the descriptive analysis methodology by approaching somegender concepts from Holmes and Oakley. The conclusion shows that changes in thepolitical situation and culture never allow women to develope themselves as chargedto their weakness spot. Jepson emphasized that women should pay so dearly forchanges their made.